“Efecto de cuatro dosis de trihormona en el cultivo de ají carapita (capsicum frutenscens L.) variedad nativa, bajo condiciones agroecológicas en la provincia de Lamas” - Arévalo Ramírez, Jairo Luis (2014)
The present investigation entitled "Effect of four doses of Trihormona in growing Charapita (Capsicum frute cens L.), nativa variety under agro-ecological conditions in the Province of Lamas" imed to determine the most effective dose of Trihormona in the development and pr duction of culture Charapita pepper (Capsicum frutescens L.), native variety in the rovince of Lamas. The present research was conducted from July to November 2012, the block design was completely randomized, with 5 treatments and 3 blocks The results we obtained indicate that all the variables studied hada direct relatio ship with performance. Treatment T4 (0.4 I /ha) with the highest average reached *3,472,91 Kg.ha-1 in which performance and statistically surpassed others, followed by other treatments T3 (0.3 Kg /ha) T2 (0.2 Kg I ha) T1 (0.1 Kg I ha) and TO. All treatments yielded indices B I C above zero being the treatment T4 (0.4 Trihorm na Kg.ha-1 had the best B I C with 0.64 followed by T3 (O. 3 Kg I ha-1 ). of Trihor ona T2 (0.2 Kg I ha-1) Tri hormona, T1 (O. 1 kg ha-1) of Trihormona and TO (contr 1) with values of 0.57, 0.48, 0.30 and 0.16 respectively. these results demonstrate hat increasing doses Trihormona, repercuto directly into increased performance Kg~ha-1 and thus in increasing crop profitability Charapita chili. Keywords: pepper, Charapi~a, variety, native, Trihormona